Hubungan Organizational Citinzenship Behavior, Kepemimpinan Melayani Dan Budaya Organisasi Guru Sd Di Kecamatan Cilongok Kabupaten Banyumas - Nugroho, Roko Adi; Jazuli, Akhmad (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE RELATIONSHIP OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR, SERVICE LEADERSHIP, AND ORGANIZATIONAL CULTURE OF PRIMARY TEACHERS IN CILONGOK DISTRICT, BANYUMAS REGENCYThis research aims to find efforts that can be made to improve teacher Organizational Citizenship Behavior through a study of its relationship with servant leadership and organizational culture. The population of this study was 219 civil servant teachers, with a total sample of 142 teachers whose determination used the Slovin formula with an error tolerance of 5%. Data was collected using instruments in questionnaires and analyzed using descriptive and inferential statistical analysis. The results showed three positive and significant relationships. First, a positive and significant relationship exists between servant leadership and organizational citizenship behavior among civil servant teachers, with a correlation coefficient of 0.430. Second, a positive and significant relationship exists between organizational culture and teacher Organizational Citizenship Behavior, with a correlation coefficient of 0.516. Third, a positive and significant relationship exists between servant leadership and organizational culture and teacher Organizational Citizenship Behavior with a correlation coefficient of 0.618.